CORRELATION OF LIP PRINTS WITH PALATAL RUGAE - P, Deekshetha; K, Don; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Human identification is necessary for personal, social, and legal reasons. Lip print patterns and Palatal Rugae, taken from the scene of crime, constitute very important supplementary aids for crime detection and jurisprudence. They are permanent, unchangeable even after death, and unique to each person. The main aim of this research is to find if there is any correlation between the occurrence of lip prints and palatal rugs and gender. Positive identification of a living or deceased person using distinctive traits is a cornerstone of forensic science. This requires a combination of different procedures. Correlating lip prints and palatal rugae with gender may be more valuable in forensic science in precise identification of an individual than by means of lip prints or palatal rugae alone. If any correlation can be established, it can create a new room in forensic odontology investigation.The aim of this study was to assess the correlation of lip print patterns with palatal rugae patterns in gender determination.